KELAYAKAN E-MODUL FLOW VIRTUAL SIMULATION BERBASIS MACROMEDIA FLASH - Ilmi Ariyanti; Albertus Djoko Lesmono; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract The purpose of this research is to describing the validity of e-module flow virtual simulation based on macromedia flash. This research were developed by IDI (Instructional Development Institute) which has three major stages of the system approach, namely the stage of defining, developinng, and evaluating. Validation is done by the validator,the resuslts of the validaty analysis show that e-module flow virtual simulation based on macromedia flash included in valid criteria with the average overall aspect (Va) is 3.5. Key word: validity, e-module, virtual simulation, macromedia flash